Risco ambiental gerado pelo uso de antibióticos no setor de internamento pediátrico hospitalar - Guerra, José Angelo (2017)
High consumption of antibiotics, which raises concerns about super bacteria in hospitals, means they are ideal for studying the fate and effects of residual antibiotics in the environment. Hospital effluents have always been a source of alarm for microbiological pollution, but only with the increased detection of antibiotics in rivers bodies did the necessity to evaluate their environmental risk arise. In this context, an environmental risk assessment (ERA) was conducted for 19 antibiotics used by a hospital pediatric inpatient sector over the course of 36 months (June 2013 to June 2016). The main objective of this study was to estimate the environmental risk associated with the standard use of the selected antibiotics. The method known as the Predict Environmental Concentration (PEC) Phase I and Phase II (EMeA, 2006) was employed. Data comprised of the population and drug consumption to calculate the PEC, and referenced values for the Predict No-Effect Concentration (PNEC) were obtained from the literature. The Risk Quotient (RQ), used to characterize the risk, was obtained via the ratio PEC/PNEC. Just four antibiotics had values below the trigger level (RQ <1), the other fifteen presented RQ values considered to have a high potential to damage the environment. Ceftriaxone, piperacillin, tazobactam, ciprofloxacin, vancomycin and oxacillin presented the highest scores. The results evidence that there is environmental risk associated with the discharge of these substances, representing a significant environmental concern in relation to the standard consumption of antibiotics in the hospital pediatric inpatient sector.